Blending Beauty and the Beast: Metamorphic Body Regimes of a Somatic Society - Kérchy, Anna (Hungarian Journal of English and American Studies, 2020)
Book review:Steinhoff, Heike. Transforming Bodies: Makeovers and Monstrosities in American Culture. Houndmills, Basingstoke: Palgrave Macmillan, 2015. ix + 267 pages. ISBN 978-1-137-49378-1. Hb. €85.59.